The effect of internal control systems and accessibility on accountability and its impact on fraud in village financial management - Siallagan, Hamonangan; Sinurat, Mangasa; Lumban Gaol, Vebry Mardomdom; Hasugian, Christnova; Irianto, Tomi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Villages are public sector organizations, so accountability is an important principle that must be reflected in their financial management. The accountability in managing the village funds is a demand for the local government as the village funds manager, as an implementation of the constitution number 6, 2014. The existed influence factor of the accountability in managing the village funds are internal control systems and accessibility. Increasing accountability in village fund management, the potential for fraud in fund management can be reduced. This research aim to determine the effect of internal control systems and accessibility of financial reports on accountability of village financial management, and the effect of accountability of village financial management on the potential for fraud in village financial management. The primary data used in this research were acquired by administering questionnaires to respondents. A total of 115 questionnaires were distributed directly to 29 villages in Samosir Regency. Rate of returned and completed questionnaire is 100%. Data analysis was carried out using the PLS with WarpPLS 7.0 software. The research results supported all hypotheses and found that; 1. internal control systems positively significant affect the accountability of village financial management, 2. accessibility of financial reports positively significant affect the accountability of village financial management and 3. The accountability of village financial management negatively significant affects the potential for fraud in village financial management. The research results indicated that The Internal Control System has a greater influence than accessibility. This in turn implies that the public would consider that village financial management is accountable if its financial report is prepared in accordance with the applicable standards and easily accessed. In addition, the potential for fraud will be reduced with increasing accountability in village financial management. These results expect the village government to improve internal control and accessibility in managing village funds.